Treatment patterns, clinical outcomes, and costs following the approval of new systemic therapy medications for hepatocellular carcinoma. Issue 28 (1st October 2022) - Pham, Timothy; Gordon, Aliza; Debono, David Joseph; Fisch, Michael Jordan
Abstract : 398 Background: Between March 2017 and May 2020, ten new systemic medication therapies for hepatocellular carcinoma (HCC) were approved for the US market. However, clinical trials for medications only showed marginal improvement in health outcomes compared to placebo or sorafenib, the only medication previously approved for HCC. The objective of this study was to examine the change in treatment patterns and outcomes of incident patients with HCC before and after multiple medication approvals. Methods: This observational cohort study used administrative medical and pharmacy claims data for adult commercially insured and Medicare Advantage patients with at least two diagnoses of HCC during July 2013 to December 2020. Patients were categorized into two groups: the pre-approval group (identified between July 2013 and March 2017) and the post-approval group (identified between April 2017 and December 2020). We compared systemic therapy treatment (e.g., sorafenib and lenvatinib) patterns, survival, hospitalization for serious infections, other treatments such as G-CSF use and liver transplants, and cost (e.g, total all-cause costs and anti-HCC systemic therapy). Generalized linear model and Cox proportional hazards regression were used to assess the effect of new approvals on outcomes while controlling for baseline characteristics. Results: We identified 2, 730 patients in the pre-approval group and 2, 290 patients in the post-approval group. After risk adjustment, the latter was more likely to use systemic therapy medications (20.4% vs. 13.7%, adjusted odds ratio [aOR] 1.41, 95% confidence interval [CI] 1.22-1.62). Overall survival remained similar between the two groups (adjusted hazard ratio [HR] 0.96, 95% CI 0.87-1.06) and among the subsets who used systemic therapy (aHR 1.10, 95% CI 0.91-1.32). Odds of liver transplant (aOR 1.03, 95% CI 0.80-1.34) and hospitalization for serious infections (aOR 0.95, 95% CI 0.87-1.09) were similar, while the post-approval group had lower odds of G-CSF use (aOR 0.59, 95% CI 0.48-0.73). No differences in total per-member-per-month (PMPM) costs were seen, but the post-approval group had lower PMPM pharmacy-related costs (adj cost diff -$1, 188, 95% CI -$1, 575 to -$755) and higher PMPM systemic therapy costs (adj cost diff $971, 95% CI $584 to $1446). Conclusions: As expected, use of newer systemic therapies in HCC patients increased following approval of new medications. However, there was no associated change in clinical outcomes such as survival or serious infections, providing additional real-world evidence of marginal improvement, if any. Pharmacy costs decreased in the post-approval group, which may reflect a shift from oral sorafenib to newer injectable systemic therapies.